RELEVANCE OF GANDHI PHILOSOPHY: गाँधी-दर्शन की प्रासंगिकता - Parveen, Heena (International Journal of Research -GRANTHAALAYAH, 2018)
The basic elements of Gandhi philosophy are truth, non-violence and love and on this basis, the bells of political, religious and economic ideas are flourishing. These three elements are nurturing and fostering the entire Gandhi-darshan like light, water and air. Through the article presented, we will see the essentiality and relevance of Gandhi philosophy in the present society. गाँधी-दर्शन के आधार तत्व सत्य, अहिंसा और प्रेम हैं और इसी आधार पर राजनीतिक, धार्मिक और आर्थिक विचारों की बेल फल-फूल रही है। यही तीन तत्व प्रकाश, जल और वायु की भँाति सम्पूर्ण गाँधी-दर्शन को पोषित व पल्लवित कर रहे हैं। प्रस्तुत आलेख द्वारा हम वर्तमान समाज में गाँधी-दर्शन की अनिवार्यता तथा प्रासंगिकता अवलोकन करेंगे।